2021
DOI: 10.1038/s41598-021-03751-5
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted functional connectivity in PD with probable RBD and its cognitive correlates

Abstract: Recent studies associated rapid eye movement sleep behavior disorder (RBD) in Parkinson’s disease (PD) with severe cognitive impairment and brain atrophy. However, whole-brain functional connectivity has never been explored in this group of PD patients. In this study, whole-brain network-based statistics and graph-theoretical approaches were used to characterize resting-state interregional functional connectivity in PD with probable RBD (PD-pRBD) and its relationship with cognition. Our sample consisted of 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 42 publications
4
14
0
Order By: Relevance
“…52,53 Previous MRI studies have demonstrated that the functional connectivity between the superior occipital gyrus and the superior parietal gyrus, the precuneus and posterior cingulate gyrus were decreased in patients with PD-RBD, which were related to the poor visuospatial-executive function. 8,54,55 These results concurred with our study, where the decreased brain activity in the posterior regions and significant differences in the score of visuospatial-executive function was exhibited in the PD-RBD group relative to the HCs, suggesting that the PD-RBD group may represent more serious neurodegeneration in terms of cognitive impairment, especially the visuospatial-executive impairment. 3 In addition, Hu et al have demonstrated that visuospatial-executive function impairment might predict the progression of mild cognitive impairment, 6 and a longitudinal follow-up study should be conducted.…”
supporting
confidence: 90%
“…52,53 Previous MRI studies have demonstrated that the functional connectivity between the superior occipital gyrus and the superior parietal gyrus, the precuneus and posterior cingulate gyrus were decreased in patients with PD-RBD, which were related to the poor visuospatial-executive function. 8,54,55 These results concurred with our study, where the decreased brain activity in the posterior regions and significant differences in the score of visuospatial-executive function was exhibited in the PD-RBD group relative to the HCs, suggesting that the PD-RBD group may represent more serious neurodegeneration in terms of cognitive impairment, especially the visuospatial-executive impairment. 3 In addition, Hu et al have demonstrated that visuospatial-executive function impairment might predict the progression of mild cognitive impairment, 6 and a longitudinal follow-up study should be conducted.…”
supporting
confidence: 90%
“…The study also used graph theory analysis to find increased normalized characteristic path length, as a global graph measure, in PD patients with probable RBD compared with PD patients. This finding was also present when comparing PD patients with and without probable RBD stratified by the presence of mild cognitive impairment (i.e., increased normalized characteristic path length in PD patients with probable RBD with MCI in comparison to PD patients with MCI and without RBD) (Oltra et al, 2021). Having a longer path length means this network is less efficient overall in integrating information at the whole‐brain level.…”
Section: Functional Imaging Abnormalitiesmentioning
confidence: 86%
“…In a study that explored the whole‐brain functional connectivity differences between PD patients with and without probable RBD using a threshold‐free network‐based approach, authors found that medicated PD patients with probable RBD had reduced functional connectivity between the right ventral posterior cingulate and left medial precuneus compared to PD patients without RBD. In addition, PD patients with probable RBD had reduced connectivity between the cingulate cortex and temporal, frontal, insular, and thalamic regions compared to healthy controls (Oltra et al, 2021). These functional connectivity abnormalities were associated with the visuo‐perceptual function in PD patients with probable RBD.…”
Section: Functional Imaging Abnormalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding sleep disorders, PD patients with rapid eye movement sleep behavior disorder (RBD) had reduced functional connectivity to temporal, frontal, insular and thalamic regions when compared to healthy controls. When compared to PD patients without RBD, PD patients with RBD had a reduced connectivity between posterior cingulate and precuneus [ 181 ]. PD patients with pain relieved under deep brain stimulation showed a reduced activity of the anterior cingulate in fMRI as compared to those without relief of pain [ 182 ], with a positive correlation between DAT binding in the posterior cingulate and the pain threshold [ 183 ].…”
Section: Regions Of the Limbic Systemmentioning
confidence: 99%